2017
DOI: 10.1038/s41550-017-0166
|View full text |Cite
|
Sign up to set email alerts
|

Blue large-amplitude pulsators as a new class of variable stars

Abstract: Regular intrinsic brightness variations observed in many stars are caused by pulsations. These pulsations provide information on the global and structural parameters of the star. The pulsation periods range from seconds to years, depending on the compactness of the star and properties of the matter that forms its outer layers. Here, we report the discovery of more than a dozen of previously unknown short-period variable stars: blue large-amplitude pulsators. These objects show very regular brightness variation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
237
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(256 citation statements)
references
References 31 publications
18
237
1
Order By: Relevance
“…The source in one of our events, PAR-42, has been observed spectroscopically with the 2.5m Irénée du Pont telescope at Las Campanas Observatory in April 2014 (see Pietrukowicz et al 2015 for details). The low-resolution spectra, obtained with the B&C spectrograph, clearly showed that the source is a K3 Red Clump Giant, confirming our conclusions based solely on the CMD from OGLE-III.…”
Section: Colour-magnitude Diagram Selectionmentioning
confidence: 99%
“…The source in one of our events, PAR-42, has been observed spectroscopically with the 2.5m Irénée du Pont telescope at Las Campanas Observatory in April 2014 (see Pietrukowicz et al 2015 for details). The low-resolution spectra, obtained with the B&C spectrograph, clearly showed that the source is a K3 Red Clump Giant, confirming our conclusions based solely on the CMD from OGLE-III.…”
Section: Colour-magnitude Diagram Selectionmentioning
confidence: 99%
“…The variable star population of the cluster includes RR Lyrae, long-period semi-regular variables, short-period eclipsing binaries and an X-ray source whose counterpart presents optical variability (Pietrukowicz & Kaluzny 2004;Homer et al 1996). The Catalogue of Variable Stars in Globular Clusters (CVSGC) (Clement et al 2001), in its 2015 edition, lists 28 confirmed variables and summarises the history of their discovery between 1917 and 2004.…”
Section: Introductionmentioning
confidence: 99%
“…OGLE-GD-DSCT-0058 is a star in the Galactic disk which was initially classified as a δ Sct star ( [28]). Its period is only 28 minutes, it has a large amplitude, and its light curve morphology is typical for fundamental-mode pulsating stars.…”
Section: Blue Pulsating Starsmentioning
confidence: 99%
“…This project was conducted from 1990 to 2003 and it was divided into two phases. In the first phase (EROS-1), it used two telescopes located at the ESO La Silla Observatory in Chile: a 1-meter Schmidt telescope and a [28], [51], [54] Long-Period Variables LMC, SMC, GB 343 785 [43], [47], [49] δ Scuti stars LMC, GD 2 844 [28], [35] Eclipsing and ellipsoidal LMC, SMC, GB, GD 510 792 [24], [27], [55] binary systems Total 951 614 1 GB = Galactic bulge; GD = Galactic disk. 0.4-meter telescope equipped with a CCD camera.…”
Section: Introductionmentioning
confidence: 99%